2017
DOI: 10.1007/s12639-017-0923-5
|View full text |Cite
|
Sign up to set email alerts
|

A report on two new myxozoan parasites infecting gills of fingerlings of Indian major carps cultured in nursery ponds in Punjab (India)

Abstract: This paper presents the morphological characteristics of two new species belonging to the genus viz n. sp. and n. sp., parasites infecting gill lamellae and gill filaments of fingerlings of (Ham.) and (Ham.) respectively collected from nursery ponds located in the village Fagan Majra, District Fatehgarh Sahib, Punjab (India). A total of 90 fingerlings were examined (40 and 50 ). Out of which, 32 and 19 fishes were found infected. The total prevalence rate was recorded as 56.66%. The age of the fish was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In total, 10 species of myxosporean parasites belonging to the genus Myxobolus i.e. M. knobii Kaur and Ahmad (2017); M. majraiensis Kaur and Ahmad (2017); M. markiwi Kaur and Ahmad (2016); M. naini Kaur and Singh (2008); M. nanokiensis ; M.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 10 species of myxosporean parasites belonging to the genus Myxobolus i.e. M. knobii Kaur and Ahmad (2017); M. majraiensis Kaur and Ahmad (2017); M. markiwi Kaur and Ahmad (2016); M. naini Kaur and Singh (2008); M. nanokiensis ; M.…”
Section: Resultsmentioning
confidence: 99%
“…In most aquatic ecosystems, fishes are hosts to parasites, and sometimes, these parasites can affect fish biology and health (7)(8)(9)(10). Some of the most dramatic cases occur when fishes are intermediate hosts for parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most dramatic cases occur when fishes are intermediate hosts for parasites. It has been shown that parasites reduce fish production, affect fish health, make fish more vulnerable to other infections, and even result in fish deaths (11)(12)(13). Fish parasites lead to a reduction in economic returns and a decline in the availability of fish as protein-rich sources (14).…”
Section: Introductionmentioning
confidence: 99%